2023
DOI: 10.1097/nan.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Midline Catheter Complications Among Hospitalized Patients

Abstract: The Art and Science of Infusion Nursing BACKGROUND Inpatient use of midline catheters has increased as a strategy to reduce excessive use of central venous access devices (CVADs) and risk of central-line associated bloodstream infections. 1,2 In addition, a midline catheter is recommended for therapy lasting 5 to 14 days, providing a longer catheter dwell time than short peripheral intravenous catheters. Use of midline catheters may remain appropriate for therapy up to 28 days depending on patient vasculature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Compared to CVCs, midline catheters have lower risks of catheter related blood stream infection and thrombosis; the risk of thrombophlebitis is lower compared to peripheral catheters 10 . Cited rates for midlines include those of infection: 0.0%–0.3%; phlebitis: 0.3%–1.7%; infiltration or extravasation: 3.5%–10%; and occlusion: 2.6%–17.0% 11,12 . Other risks associated with midlines include erythema at the insertion site, bleeding, and pain 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to CVCs, midline catheters have lower risks of catheter related blood stream infection and thrombosis; the risk of thrombophlebitis is lower compared to peripheral catheters 10 . Cited rates for midlines include those of infection: 0.0%–0.3%; phlebitis: 0.3%–1.7%; infiltration or extravasation: 3.5%–10%; and occlusion: 2.6%–17.0% 11,12 . Other risks associated with midlines include erythema at the insertion site, bleeding, and pain 13 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Cited rates for midlines include those of infection: 0.0%-0.3%; phlebitis: 0.3%-1.7%; infiltration or extravasation: 3.5%-10%; and occlusion: 2.6%-17.0%. 11,12 Other risks associated with midlines include erythema at the insertion site, bleeding, and pain. 13 These complications are spread over an average dwell time for midline catheters of 7.7-16.7 days, 10 which is longer than needed for stem cell collection.…”
Section: Logistical Issues Associated With Line Placementmentioning
confidence: 99%
“…Su inserción se ha definido como el procedimiento invasivo más frecuente en todo el mundo y estos presentan una alta tasa de complicaciones asociado al 8% -42%. Dentro de las complicaciones se informan oclusión, sangrado en el sitio de inserción, infiltración y extravasación, trombosis relacionada al catéter, flebitis, retiro accidental e infección (2)(3)(4)(5)(6).…”
Section: Introduccionunclassified
“…2 Complications may include phlebitis, post-insertion phlebitis, pain, discomfort, occlusion, infiltration, extravasation, thrombosis, nerve injury, or PIVC-related bloodstream infections. 2,9,10 PIVC infection prevention and safety is a concern for patients 2 and the literature is unclear as to what extent patients are monitored for complications, especially post-infusion. In their study, Webster et al found that 75% of patients with post-infusion phlebitis did not initially have phlebitis upon the removal of the PIVC.…”
Section: Introductionmentioning
confidence: 99%
“…A significant challenge in PIVC management is preventing and dealing with PIVC-related complications, which are costly both to the patient and to the health care system 2 . Complications may include phlebitis, post-insertion phlebitis, pain, discomfort, occlusion, infiltration, extravasation, thrombosis, nerve injury, or PIVC-related bloodstream infections 2,9,10 . PIVC infection prevention and safety is a concern for patients 2 and the literature is unclear as to what extent patients are monitored for complications, especially post-infusion.…”
Section: Introductionmentioning
confidence: 99%